PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE INSTANT ASSESSMENT TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWAKELAS VII SMPN 3 KOTO XI TARUSAN KABUPATEN PESISIR SELATAN - Muharani, Dehan; Haryono, Yulia; Lovia, Lita (Pendidikan Matematika, 2014)
Â ABSTRACTÂ This research was carried out due yo the studentsâ low learning achievement in mathematics in class VII SMPN 3 Koto XI Tarusan Kabupaten Pesisir Selatan. This research was aimed at revealing whether the mathematics conceptual understanding of the studentsâtaught by using instant assessment active learning was better than that of studentsâ taught by using conventional learning. This was an experimental research which used random toward the subject design. Based on the result of data analysis it was found that the two sample classes were normally distributed and homogenous. Furthermore, the result of t-test indicated that the value of Â was higher than Â in which Î± was 0.05. this result showed that the mathematics conceptual understanding of the studentsâ taught by using instant assessment active learning was better than of studentsâ taught by using conventional learning in class VII SMPN 3 Koto XI Tarusan Kabupaten Pesisir Selatan registered in academic year 2013/2014.